2021
DOI: 10.1002/er.6935
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the neutronic performance of thorium mixed with uranium or plutonium in a high‐temperature pebble‐bed reactor

Abstract: High-temperature gas-cooled reactors (HTGRs) present an interesting concept for the next generation of nuclear reactors due to them having many advantages. In particular, their fuel is based on coated particles known as tri-struc-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The structural components of the reactor core such as graphite reflectors were easily modeled while the coolant in the reflector side and especially, the reactor shutdown and control systems require special effort in modeling. The modeling and calculations performed in this study were demonstrated successfully in various publications [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Pebbles In Core Modelingmentioning
confidence: 76%
“…The structural components of the reactor core such as graphite reflectors were easily modeled while the coolant in the reflector side and especially, the reactor shutdown and control systems require special effort in modeling. The modeling and calculations performed in this study were demonstrated successfully in various publications [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Pebbles In Core Modelingmentioning
confidence: 76%
“…Thorium‐based fuel is one example of such an alternative fuel technology. Thorium and its based fuels have the lowest neutron poison productions (eg, Xenon and Samarium), and the addition of thorium could reduce the amount of burnable poison required 6 . Thorium‐based fuel has also higher thermal conductivity than uranium‐based fuel, especially at low temperatures, and its thermal expansion is less than that of uranium‐based fuel, and its melting point is very high (3300°C) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Thorium‐based fuel has also higher thermal conductivity than uranium‐based fuel, especially at low temperatures, and its thermal expansion is less than that of uranium‐based fuel, and its melting point is very high (3300°C) 7 . However, because thorium, primarily in the form of Th‐232, is a fertile material, it must be combined with a fissile nucleus such as U‐235, or U‐233 and Pu‐239, to initiate the fuel cycle 6 . Thorium‐based fuel cycle contributions have been thoroughly examined as potential replacements for many established reactor technologies such as molten salt reactors, 8,9 advanced prismatic and pebble‐bed high‐temperature reactors, 4,6,10 as well as Generation III and III+ pressurized water reactors 10‐12 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations